Protein Kinase C Activation as a Potential Therapeutic Strategy in Alzheimer's Disease: Is there a Role for Embryonic Lethal Abnormal Vision‐like Proteins?. Issue 2 (29th April 2016) - Talman, Virpi; Pascale, Alessia; Jäntti, Maria; Amadio, Marialaura; Tuominen, Raimo K.
Abstract: Alzheimer's disease (AD), the most common cause of dementia, is an irreversible and progressive neurodegenerative disorder. It affects predominantly brain areas that are critical for memory and learning and is characterized by two main pathological hallmarks: extracellular amyloid plaques and intracellular neurofibrillary tangles. Protein kinase C (PKC) has been classified as one of the cognitive kinases controlling memory and learning. By regulating several signalling pathways involved in amyloid and tau pathologies, it also plays an inhibitory role in AD pathophysiology. Among downstream targets of PKC are the embryonic lethal abnormal vision (ELAV)‐like RNA‐binding proteins that modulate the stability and the translation of specific target mRNAs involved in synaptic remodelling linked to cognitive processes. This MiniReview summarizes the current evidence on the role of PKC and ELAV‐like proteins in learning and memory, highlighting how their derangement can contribute to AD pathophysiology. This last aspect emphasizes the potential of pharmacological activation of PKC as a promising therapeutic strategy for the treatment of AD.